Evaluating two live-attenuated vaccines against Salmonella enterica serovar Reading in turkeys: reduced tissue colonization and cecal tonsil transcriptome responses - Monson, Melissa S.; Gurung, Manoj; Bearson, Bradley L.; Whelan, Samuel J.; Trachsel, Julian M.; Looft, Torey; Sylte, Matthew J.; Bearson, Shawn M.D. (Frontiers in Veterinary Science, 2024)
Vaccines that cross-protect across serovars of Salmonella enterica (Salmonella) would be a beneficial intervention against emerging and persistent Salmonella isolates of concern for the turkey industry. The 2017–2019 foodborne outbreak of Salmonella enterica serovar Reading (S. Reading) revealed the need for effective control of this serovar in turkey production. This study evaluated two live-attenuated Salmonella vaccines, an internally developed cross-protective vaccine and a commercially available vaccine, against an outbreak-associated strain of S. Reading in turkeys. At 1 day and 3 weeks of age, male turkey poults were either mock-vaccinated with phosphate buffered saline (PBS) or given one of the vaccines by oral gavage (primary and booster) or aerosol spray (primary) then drinking water (booster). At 7 weeks of age, poults were challenged with 109 colony forming units (CFU) of S. Reading; a mock-vaccinated group was mock-challenged with PBS. Colonization of the cecal contents and cecal tonsil was 1.5–3 log10 CFU/g lower in vaccinated birds than mock-vaccinated birds at 7 and/or 14 days post-inoculation (DPI). Salmonella dissemination to the spleen was significantly reduced by both vaccines. Gene expression of intestinal transporters (such as SCNN1B and SLC10A2) and tight junction proteins was significantly decreased in the turkey cecal tonsil transcriptome at 2 DPI with S. Reading. Vaccination with either vaccine mitigated most cecal tonsil gene expression responses to S. Reading challenge. Therefore, both the internally developed vaccine and commercial vaccine were cross-protective against colonization and dissemination, and both were able to limit transcriptional changes from challenge in intestinal health-related genes in the cecal tonsil, thereby providing vaccination efficacy and impact data against S. Reading in turkeys.